Smart contracts: conceitos, limitações e potencialidades - Gabriel Gonçalves Santos (2022)
In this work, it is investigated a new legal-computational phenomenon: smart contracts, through a transdisciplinary methodology. It seeks: in Chapter 1, to understand the technology that enables the existence of these contracts; in Chapter 2, to analyze smart contracts both the “is” (ontological) and the “ought” (deontological) points of views, as well as if smart contracts are in fact contracts in the legal sense; in Chapter 3, to ponder the idea of Lex Cryptographia, identify sticking points that smart contracts generate in face of the legal system and potential solutions presented by academic literature. Throughout this dissertation, real and hypothetical examples of smart contracts are brought, to which it is intended to reflect the theoretical discussions, including the conception of Lawrence Lessig about the four modalities to constrain users' behavior in cyberspace.